Criminal Conviction of Social Workers in the Criminal Justice System - Christin Novianty Panjaitan; Afriyanti Debora Tambunan; Richard Wilson Antonius; Lutfiadi Lutfiadi (LEGAL BRIEF, 2023)
This study aims to analyze the concept of social worker sentencing policy, and to know the criminal law of social work as a solution to reduce overcapacity in Indonesian Correctional Institutions. This study uses a normative juridical method with analytical descriptive specifications. The findings showed that the current policy of imposing criminal sanctions is felt to be ineffective because every criminal who is proven and has the power of law to carry out legal proceedings in prison is still not appropriate if the weight of the crime is a minor offenses. As a solution, the imposition of criminal sanctions on social workers has been determined to be appropriate. It is necessary to have a criminal law policy so that what becomes a legal issue can be resolved effectively, likewise with the effectiveness of the provision of prison sentences, which are no longer in accordance with prison conditions, leading to an increase of 500 to 900 percent, which eliminates the duties and functions of Correctional Institutions as a coaching and protection institution for convicts. In conclusion, the policy of imposing criminal penalties on social workers is appropriate in order to reduce over capacity.